Rare earth cerium doped copper / molybdenum dioxide heterogeneous material and preparation method and application thereof
By using metal-organic precursor-mediated strategies to prepare rare earth cerium-doped copper/molybdenum dioxide heterogeneous materials in the process of electrochemical nitrate reduction and synthesis, the problem of low selectivity of single copper center material was solved and efficient ammonia synthesis was achieved.
Patent Information
- Application Number
- CN202411962156.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
A single copper central material has difficulty in developing a hydrogen-mediated reduction path, resulting in low selectivity during the electrochemical nitrate reduction and synthesis of ammonia.
The rare earth cerium-doped copper/molybdenum dioxide heterogeneous materials were prepared by using metal-organic precursor mediation strategy, and Ce-Cu/MoO2 nanomaterial with pomegranate seed-like structure was formed through co-precipitation and high-temperature calcination.
Under alkaline conditions, Ce-Cu/MoO2 nanomaterials exhibit high ammonia production rate and Faraday efficiency, significantly improving catalytic performance.
Smart Images

Figure CN119771448A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material preparation, and specifically relates to a rare earth cerium doped copper / molybdenum dioxide heterogeneous material and a preparation and application thereof. Background Art
[0002] The ammonia industry forms the basis of modern agriculture and human society. 3 ) is also considered to be the future hydrogen storage fuel, with a hydrogen storage capacity of up to 17.6wt%. At present, the world's ammonia production is achieved through the traditional Haber-Bosch process, which requires high temperature and high pressure reaction conditions, consumes a lot of energy and releases a lot of carbon dioxide. Therefore, using electricity generated by renewable energy such as solar energy, wind energy and tidal energy to synthesize ammonia by electrochemical catalysis is considered to be a new technology for green ammonia synthesis in the future.
[0003] Electrochemical nitrate reduction involves a complex process of 8 electrons and 9 protons, involving many intermediates and products. Therefore, it is of great significance to develop high-performance electrocatalytic materials to efficiently and selectively reduce nitrate to ammonia. Currently, copper-based materials have received extensive attention in the field of nitrate reduction to synthesize ammonia. However, since a single copper center is difficult to provide the active adsorbed hydrogen atoms required for the catalytic reaction, it is difficult to occur an active hydrogen-mediated reduction pathway, and the selectivity of synthesizing ammonia is low.
[0004] Rare earth elements and their compounds are important strategic resources and are widely used in aviation, aerospace, information, electronics, energy, transportation, medical and health care and other fields. The "Rare Earth Management Regulations" implemented on October 1, 2024 clearly encourage and support the research and development and application of new technologies, new processes, new products, new materials and new equipment in the rare earth industry. Cerium oxide has high reserves, low prices and good stability, and has been deeply studied in the field of catalysis. At present, a large number of studies have introduced cerium oxide or rare earth cerium ions into active materials to regulate the surface microstructure and electronic structure of the active center of the active materials, thereby improving their catalytic performance in the electrochemical water decomposition reaction (Appl. Catal. B: Environ. 2024, 343, 123560, Small 2022, 18, 2106592, Chem. Eng. J. 2023, 460, 141119, Inorg. Chem. 2024, 63, 16824 Adv. Energy Mater. 2024, DOI: 10.1002 / aenm.202402923, Angew. Chem. Int. Ed. 2024, DOI: 10.1002 / anie.202415306).
[0005] In view of the difficulty of the single copper center material mentioned above to undergo active hydrogen-mediated reduction pathways, most existing research and technologies use transition metal nickel or cobalt centers to optimize active hydrogen-mediated reduction pathways, which promotes the catalytic process to a certain extent, and it is necessary to introduce new centers to optimize the structure to achieve further improvement in catalytic performance. Currently, there are few studies on the introduction of rare earths into active copper-based materials. Therefore, the present invention adopts a metal organic precursor-mediated strategy to prepare rare earth cerium-doped copper / molybdenum dioxide heterogeneous materials, which has a vital application value for electrochemical nitrate reduction to synthesize ammonia. Summary of the invention
[0006] The purpose of the present invention is to provide a rare earth cerium doped copper / molybdenum dioxide heterogeneous material and a preparation method and application thereof. When the material of the present invention is used as a catalyst, it exhibits a high ammonia production rate and Faraday efficiency for nitrate reduction to synthesize ammonia under alkaline conditions.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The present invention first provides a method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material, comprising:
[0009] Step 1: dissolving rare earth cerium salt, copper salt, molybdenum salt and coordination modulator in water, stirring evenly to obtain a metal salt solution, pouring the organic ligand solution into the metal salt solution, stirring evenly to obtain a rare earth cerium doped metal organic precursor nanomaterial;
[0010] Step 2: Under the protection of an inert atmosphere, the rare earth cerium-doped metal organic precursor nanomaterial obtained in step 1 is placed in a tubular furnace and calcined to obtain a rare earth cerium-doped copper / molybdenum dioxide heterogeneous material.
[0011] Preferably, the molar ratio of the rare earth cerium salt, copper salt, molybdenum salt and coordination modulator in step 1 is (0.5-5):(40-60):(6-15):(20-40), and the molar ratio of the copper salt to the organic ligand is (40-60):(30-50).
[0012] Preferably, the cerium salt is cerium nitrate, cerium chloride or cerium acetate.
[0013] Preferably, the copper salt is copper nitrate, copper chloride or copper acetate.
[0014] Preferably, the molybdenum salt is ammonium heptamolybdate or phosphomolybdic acid.
[0015] Preferably, the coordination modulator is L-aspartic acid, L-alanine or L-glutamic acid.
[0016] Preferably, the organic ligand is trimesic acid, terephthalic acid or thiophenedicarboxylic acid.
[0017] Preferably, the calcination temperature in step 2 is 600° C. to 900° C., and the calcination time is 1 to 4 hours.
[0018] The present invention also provides a rare earth cerium doped copper / molybdenum dioxide heterogeneous material obtained by the above preparation method, wherein the material has a pomegranate seed-like structure.
[0019] The present invention also provides the use of the rare earth cerium doped copper / molybdenum dioxide heterogeneous material as a catalyst in the synthesis of ammonia by nitrate reduction.
[0020] Beneficial effects of the present invention
[0021] The present invention provides a rare earth cerium doped copper / molybdenum dioxide heterogeneous material and a preparation method and application thereof. The material of the present invention is prepared by a coprecipitation method under the control of a coordination modulator to prepare a rare earth cerium doped copper-molybdenum-based metal organic precursor, and then a high-temperature calcination method under the protection of an inert atmosphere is used to prepare a cerium doped copper / molybdenum dioxide heterogeneous material (Ce-Cu / MoO 2 ), the introduction of rare earth cerium in the present invention can regulate the electronic state of the copper center in the material, and cerium can serve as the center for water dissociation to produce active hydrogen, thereby forming a dual-center catalytic material and improving the catalytic performance of the material. Ce-Cu / MoO prepared by the present invention 2 The nanomaterial has a unique pomegranate seed-like structure. When used as a catalyst, it exhibits a high ammonia production rate and Faraday efficiency for nitrate reduction to synthesize ammonia under alkaline conditions. In addition, the preparation method is simple, the raw materials are easily available, and the practical value is high, which is of great significance for the design, preparation and application of catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the cerium-doped copper-molybdenum-based metal organic precursor prepared in Example 1.
[0023] Figure 2 is Ce-Cu / MoO in Example 1 2 XRD patterns of nanomaterials.
[0024] Figure 3 For Ce-Cu / MoO in Example 5 2 Polarization curves of nanomaterials in different electrolytes.
[0025] Figure 4 For Ce-Cu / MoO in Example 6 2 With Cu / MoO 2 XPS pattern of Cu in nanomaterials.
[0026] Figure 5 Ce-Cu / MoO tested in Example 7 2 With Cu / MoO2 Catalytic properties of nanomaterials. DETAILED DESCRIPTION
[0027] The present invention first provides a method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material, comprising:
[0028] Step 1: dissolving rare earth cerium salt, copper salt, molybdenum salt and coordination modulator in water, controlling the molar ratio of the four to preferably 0.5-5:40-60:6-15:20-40, and stirring evenly at room temperature to obtain a metal salt solution; dissolving an organic ligand in a solvent, the solvent is preferably ethanol, controlling the molar ratio of copper salt to organic ligand to preferably 40-60:30-50, pouring the organic ligand solution into the above metal salt solution, stirring evenly, the stirring time is preferably 6-14h, washing the obtained product with deionized water and ethanol respectively by centrifugation and drying, the drying temperature is preferably 50-80°C, the drying time is preferably 8-24h, more preferably 8-12h, to obtain a rare earth cerium doped metal organic precursor nanomaterial;
[0029] The cerium salt is preferably cerium nitrate, cerium chloride or cerium acetate; the copper salt is preferably copper nitrate, copper chloride or copper acetate; the molybdenum salt is preferably ammonium heptamolybdate or phosphomolybdic acid;
[0030] The coordination modulator is preferably L-aspartic acid, L-alanine or L-glutamic acid. The organic ligand is preferably trimesic acid, terephthalic acid or thiophenedicarboxylic acid.
[0031] Step 2: placing the cerium-doped metal organic precursor nanomaterial in a tube furnace and calcining it under the protection of an inert atmosphere, wherein the calcination temperature is preferably 600-900° C., more preferably 700-800° C., the calcination time is preferably 1-4 h, more preferably 2-3 h, and the heating rate is preferably 2-6° C. / min to obtain cerium-doped copper / molybdenum dioxide (Ce-Cu / MoO 2 )Heterogeneous nanomaterials.
[0032] The present invention also provides a rare earth cerium doped copper / molybdenum dioxide heterogeneous material obtained by the above preparation method, wherein the material has a pomegranate seed-like structure.
[0033] The present invention also provides the use of the rare earth cerium doped copper / molybdenum dioxide heterogeneous material as a catalyst in the synthesis of ammonia by nitrate reduction.
[0034] The specific implementation scheme of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0035] Example 1
[0036] Preparation of Ce-doped Copper / MoO2 Heterogeneous Nanomaterials
[0037] Cu(CH 3 COO 2 ·H 2 O (285 mg), Ce (CH 3 COO 3 ·xH 2 O (23.8 mg) was dissolved in water (60 mL) with L-glutamic acid (110 mg) and hydrated phosphomolybdic acid (450 mg), and stirred at room temperature for 30 min to form a metal salt solution; trimesic acid (211 mg) was dissolved in ethanol (60 mL), and stirred at room temperature for 10 min to form an organic ligand solution; the two solutions were then mixed and stirred at room temperature for 14 h. The obtained product was then treated with H 2 O and ethanol were centrifuged and then dried at 60 °C for 12 h to obtain the cerium-doped copper-molybdenum-based metal organic precursor nanomaterials.
[0038] The cerium-doped copper-molybdenum-based metal organic precursor nanomaterial (200 mg) was placed in a porcelain boat and placed in a tube furnace for high-temperature calcination under an argon atmosphere at a temperature of 700 °C, a heating rate of 2 °C / min, and a calcination time of 2 h to obtain Ce-Cu / MoO 2 Nanomaterials.
[0039] The morphology of the prepared Ce-doped CuMo-based metal organic precursor was characterized by scanning electron microscopy. Figure 1 As shown in the figure, it presents a smooth octahedral morphology, and the particle size is about 400nm. At the same time, the interior presents nanoparticles similar to pomegranate seeds.
[0040] Characterization of the prepared Ce-Cu / MoO by X-ray diffraction 2 The physical phase. Figure 2 As shown, the obtained Ce-Cu / MoO 2 The nanomaterials have Cu and MoO 2 of the crystalline phase.
[0041] Example 2
[0042] Preparation of Ce-doped Copper / MoO2 Heterogeneous Nanomaterials
[0043] Cu(NO 3 ) 2 ·3H 2 O (342 mg), Ce (NO 3 ) 3 6H 2O (26.6 mg) was dissolved in water (60 mL) with L-aspartic acid (55 mg) and ammonium heptamolybdate (492 mg), and stirred at room temperature for 30 min to form a metal salt solution; terephthalic acid (166 mg) was dissolved in ethanol (60 mL), and stirred at room temperature for 10 min to form an organic ligand solution; the two solutions were then mixed and stirred at room temperature for 8 h. The obtained product was then treated with H 2 O and ethanol were centrifuged and then dried at 60 °C for 8 h to obtain cerium-doped copper-molybdenum-based metal organic precursor nanomaterials.
[0044] The cerium-doped copper-molybdenum-based metal organic precursor nanomaterial (180 mg) was placed in a porcelain boat and placed in a tube furnace for high-temperature calcination under an argon atmosphere at a temperature of 800 °C, a heating rate of 5 °C / min, and a calcination time of 3 h to obtain Ce-Cu / MoO 2 Nanomaterials.
[0045] Example 3
[0046] Preparation of Ce-doped Copper / MoO2 Heterogeneous Nanomaterials
[0047] CuCl 2 ·2H 2 O (243 mg), CeCl 3 7H 2 O (22.8 mg) was dissolved in water (60 mL) with L-alanine (100 mg) and hydrated phosphomolybdic acid (600 mg), and stirred at room temperature for 30 min to form a metal salt solution; terephthalic acid (250 mg) was dissolved in ethanol (60 mL), and stirred at room temperature for 10 min to form an organic ligand solution; the two solutions were then mixed and stirred at room temperature for 10 h. The obtained product was then treated with H 2 O and ethanol were centrifuged and then dried at 70 °C for 12 h to obtain the cerium-doped copper-molybdenum-based metal organic precursor nanomaterials.
[0048] The cerium-doped copper-molybdenum-based metal organic precursor nanomaterial (240 mg) was placed in a porcelain boat and placed in a tube furnace for high-temperature calcination under an argon atmosphere at a temperature of 900 °C, a heating rate of 2 °C / min, and a calcination time of 2 h to obtain Ce-Cu / MoO 2 Nanomaterials.
[0049] Example 4
[0050] Preparation of Ce-doped Copper / MoO2 Heterogeneous Nanomaterials
[0051] Cu(CH 3 COO 2 ·H 2 O (305 mg), Ce (NO 3 )3 6H 2 O (29.6 mg) was dissolved in water (60 mL) with L-aspartic acid (128 mg) and hydrated phosphomolybdic acid (480 mg), and stirred at room temperature for 30 min to form a metal salt solution; thiophenedicarboxylic acid (220 mg) was dissolved in ethanol (60 mL), and stirred at room temperature for 10 min to form an organic ligand solution; the two solutions were then mixed and stirred at room temperature for 14 h. The obtained product was then treated with H 2 O and ethanol were centrifuged and then dried at 70 °C for 12 h to obtain the cerium-doped copper-molybdenum-based metal organic precursor nanomaterials.
[0052] The cerium-doped copper-molybdenum-based metal organic precursor nanomaterial (160 mg) was placed in a porcelain boat and placed in a tube furnace for high-temperature calcination under an argon atmosphere at a temperature of 650 °C, a heating rate of 2 °C / min, and a calcination time of 4 h to obtain Ce-Cu / MoO 2 Nanomaterials.
[0053] Comparative Example 1
[0054] Preparation of copper / molybdenum dioxide heterogeneous nanomaterials
[0055] Cu(CH 3 COO 2 ·H 2 O (285 mg), L-glutamic acid (110 mg), hydrated phosphomolybdic acid (450 mg) were dissolved in water (60 mL) and stirred at room temperature for 30 min to form a metal salt solution; trimesic acid (211 mg) was dissolved in water (60 mL) and stirred at room temperature for 10 min to form an organic ligand solution; the two solutions were then mixed and stirred at room temperature for 14 h. The obtained product was then treated with H 2 O and ethanol were centrifuged and then dried at 60 °C for 12 h to obtain copper-molybdenum-based metal organic precursor nanomaterials.
[0056] The copper-molybdenum-based metal organic precursor nanomaterial (200 mg) was placed in a porcelain boat and placed in a tube furnace for high-temperature calcination under an argon atmosphere. The calcination temperature was 700°C, the heating rate was 2°C / min, and the calcination time was 2h to obtain Cu / MoO 2 Nanomaterials.
[0057] Example 5
[0058] Ce-Cu / MoO 2 Nanomaterial catalytic performance test
[0059] The working electrode preparation process is as follows: 5 mg of the catalyst prepared in Example 1 is weighed into a 2 mL centrifuge tube, and then H 2O, 250 μL of isopropanol, and finally add 15 μL of Nafion solution, mix well and ultrasonicate for 30 minutes. Take 10 μL of the prepared ink and evenly apply it on 0.25 cm × 0.25 cm carbon paper and dry it at room temperature. Place the prepared electrode in the electrolytic cell, with the platinum sheet as the counter electrode, the Ag / AgCl electrode as the reference electrode, and 1M KOH+0.1M KNO 3 As electrolyte. Using electrochemical workstation, linear sweep voltammetry was used for testing. Figure 3 As shown, according to the pure 1M KOH and 1M KOH + 0.1M KNO 3 From the current density of the polarization curve, it can be seen that the introduction of Ce has obvious catalytic activity for nitrate reduction.
[0060] Example 6
[0061] Ce-Cu / MoO 2 With Cu / MoO 2 Nanomaterial chemical structure testing
[0062] It was characterized by XPS, such as Figure 4 As shown, the introduction of Ce changes the electronic structure of the Cu center inside the catalytic material. Therefore, doping rare earth cerium into copper-based materials through this synthesis method is of great significance for material structure regulation and improvement of electrocatalytic performance.
[0063] Example 7
[0064] Ce-Cu / MoO 2 With Cu / MoO 2 Catalytic performance of nanomaterials
[0065] The IT test was performed at a potential of -0.4 V and -0.5 V (relative to the reversible hydrogen electrode), and the color was developed by the indophenol blue method for quantitative analysis. Figure 5 As shown, Ce-Cu / MoO 2 The yield and Faraday efficiency of the nanomaterials for synthesizing ammonia were 20736.33 μg h -1 mg cat. -1 and 94.15%. Ce-Cu / MoO 2 The catalytic performance of the nanomaterial is significantly higher than that of Cu / MoO without cerium doping. 2 Nanomaterials.
Claims
1. A method for preparing rare earth cerium doped copper / molybdenum dioxide heterogeneous material, characterized in that: include: Step 1: dissolving rare earth cerium salt, copper salt, molybdenum salt and coordination modulator in water, stirring evenly to obtain a metal salt solution, pouring the organic ligand solution into the metal salt solution, stirring evenly to obtain a rare earth cerium doped metal organic precursor nanomaterial; Step 2: Under the protection of an inert atmosphere, the rare earth cerium-doped metal organic precursor nanomaterial obtained in step 1 is placed in a tubular furnace and calcined to obtain a rare earth cerium-doped copper / molybdenum dioxide heterogeneous material.
2. The method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material according to claim 1, characterized in that: The molar ratio of the rare earth cerium salt, copper salt, molybdenum salt and coordination modulator in step 1 is (0.5-5): (40-60): (6-15): (20-40), and the molar ratio of the copper salt to the organic ligand is (40-60): (30-50).
3. The method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material according to claim 1, characterized in that: The cerium salt is cerium nitrate, cerium chloride or cerium acetate.
4. The method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material according to claim 1, characterized in that: The copper salt is copper nitrate, copper chloride or copper acetate.
5. The method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material according to claim 1, characterized in that: The molybdenum salt is ammonium heptamolybdate or phosphomolybdic acid.
6. The method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material according to claim 1, characterized in that: The coordination modulator is L-aspartic acid, L-alanine or L-glutamic acid.
7. The method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material according to claim 1, characterized in that: The organic ligand is trimesic acid, terephthalic acid or thiophenedicarboxylic acid.
8. The method for preparing a rare earth cerium doped copper / molybdenum dioxide heterogeneous material according to claim 1, characterized in that: The calcination temperature in step 2 is 600° C. to 900° C., and the calcination time is 1 to 4 hours.
9. The rare earth cerium doped copper / molybdenum dioxide heterogeneous material obtained by the preparation method of claim 1, characterized in that: The material has a pomegranate seed-like structure.
10. Use of the rare earth cerium doped copper / molybdenum dioxide heterogeneous material according to claim 9 as a catalyst in the synthesis of ammonia by nitrate reduction.
Citation Information
Patent Citations
Polyacid-based supported multifunctional catalyst and preparation method thereof
CN106268964A
Alumina supported copper-rare earth metal oxide catalyst as well as preparation method and application thereof
CN113332989A
Cu-based metal organic framework and imidazole framework structure catalyst as well as preparation method and application thereof
CN113441187A
Preparation method and application of rare earth cerium doped cobalt phosphide / iron phosphide heterogeneous material
CN115305496A
Membranes comprising a layer of metal organic framework particles
WO2019186134A1